Prediction of Traction Requirements and Slippage Percentage for Three Plow Types under Various Operational Conditions - Mustafa F. Almoosa; Salim A. Almaliki; Salah M. S. Al-Atab (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2025)
This study aims to predict the traction requirements represented by draft force and slippage percentage under different soil moisture levels (7, 14, 22, and 28%), using three plows namely: - moldboard plow, chisel plow and disk plow, Three tillage depths (15, 20, 25 cm) and three forward speeds (1.83, 3.06, 5.22 km/h) were tested in clay loam soil in Qurna, Basra. Data were analyzed using Design Expert software to model draft force, slippage, and tractor performance. Based on the results obtained, it is found that the draft force increased by 62.84% and 29.05% when the depth was increased from 15 to 25 cm and the speed from 1.83 to 5.22 km h-1 respectively. Meanwhile, the slippage increased by 78.27 and 54.79% when the depth was increased from 15 to 25 cm and speed from 1.83 to 5.22 km h-1 respectively. Moreover, soil moisture at 14% gave the lowest draft force and slippage, reaching 10334 N and 12.39%, respectively, compared to other moisture levels. The results show that the use of the disk plow recorded the lowest draft force and slippage of 9966 N and 15.90%, while the use of the moldboard plow led to an increase in the draft force and slippage as it reached 12671 N and 19.02% respectively. The data analysis shows that the developed model has a good ability for prediction compared to the field data, as the coefficients of determination of the draft force and slippage are 0.9531 and 0.9480 respectively.